Flavonoids promote Rhizophagus irregularis spore germination and tomato root colonization: A target for sustainable agriculture - Lidoy, Javier; Berrio, Estefanía; García, Marta; España-Luque, Luis; Pozo, Maria J.; López-Ráez, Juan Antonio (Frontiers in Plant Science, 2023)
The use of arbuscular mycorrhizal (AM) fungi has great potential, being used as biostimulants, biofertilizers and bioprotection agents in agricultural and natural ecosystems. However, the application of AM fungal inoculants is still challenging due to the variability of results when applied in production systems. This variability is partly due to differences in symbiosis establishment. Reducing such variability and promoting symbiosis establishment is essential to improve the efficiency of the inoculants. In addition to strigolactones, flavonoids have been proposed to participate in the pre-symbiotic plant-AM fungus communication in the rhizosphere, although their role is still unclear. Here, we studied the specific function of flavonoids as signaling molecules in AM symbiosis. For that, both in vitro and in planta approaches were used to test the stimulatory effect of an array of different subclasses of flavonoids on Rhizophagus irregularis spore germination and symbiosis establishment, using physiological doses of the compounds. We show that the flavone chrysin and the flavonols quercetin and rutin were able to promote spore germination and root colonization at low doses, confirming their role as pre-symbiotic signaling molecules in AM symbiosis. The results pave the way to use these flavonoids in the formulation of AM fungal-based products to promote the symbiosis. This can improve the efficiency of commercial inoculants, and therefore, help to implement their use in sustainable agriculture.